Hunt for the Wilderpeople [videorecording (DVD)] - Dennison, Julian, 2002-; Neill, Sam; Te Wiata, Rima (Sony Pictures Home Entertainment, 2016)
Raised on hip-hop and foster care, defiant city kid Ricky gets a fresh start in the New Zealand countryside. He quickly finds himself at home with his new foster family: the loving Aunt Bella, the cantankerous Uncle Hec, and dog Tupac. When a tragedy strikes that threatens to ship Ricky to another home, both he and Hec go on the run in the bush. As a national manhunt ensues, the newly branded outlaws must face their options.